2015
DOI: 10.1039/c5cp03649f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the molecular structures of plasma-damaged and surface-repaired low-k dielectrics

Abstract: Fully understanding the effect and the molecular mechanisms of plasma damage and silylation repair on low dielectric constant (low-k) materials is essential to the design of low-k dielectrics with defined properties and the integration of low-k dielectrics into advanced interconnects of modern electronics. Here, analytical techniques including sum frequency generation vibrational spectroscopy (SFG), Fourier transform infrared spectroscopy (FTIR), contact angle goniometry (CA) and X-ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…SFG is a second-order nonlinear optical spectroscopic technique 11 44 According to the selection rule of a second-order nonlinear optical process, SFG signal can only be generated from a medium with no inversion symmetry under the electric dipole approximation 11 44 Most bulk materials possess inversion symmetry, therefore, no SFG signal can be produced.…”
Section: Metrology: Sum Frequency Generation Vibrational Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…SFG is a second-order nonlinear optical spectroscopic technique 11 44 According to the selection rule of a second-order nonlinear optical process, SFG signal can only be generated from a medium with no inversion symmetry under the electric dipole approximation 11 44 Most bulk materials possess inversion symmetry, therefore, no SFG signal can be produced.…”
Section: Metrology: Sum Frequency Generation Vibrational Spectroscopymentioning
confidence: 99%
“… 44 According to the selection rule of a second-order nonlinear optical process, SFG signal can only be generated from a medium with no inversion symmetry under the electric dipole approximation 11 44 Most bulk materials possess inversion symmetry, therefore, no SFG signal can be produced. Surfaces and interfaces lack inversion symmetry, thus, they can produce SFG signals.…”
Section: Metrology: Sum Frequency Generation Vibrational Spectroscopymentioning
confidence: 99%
“…The damaged surface can be repaired using silylation. 171 We then applied the above developed data analysis method to investigate surface and buried interfacial structures of commercial low-k samples provided by Intel and IBM. SFG was used to investigate molecular structures of surfaces and buried interfaces of pSiCOH films on Si provided by Intel.…”
Section: (11f)mentioning
confidence: 99%
“…It was reported that the surface and interfacial molecular structures of a low-k pSiCOH thin film deposited on silicon wafer could be characterized using SFG. The methodology was developed on the basis of the approach used to study polymer thin films on metal surfaces with a series of different film thicknesses. The SFG spectra collected from a model low-k film (PMSQ, Figure a, model for pSiCOH) have contributions from both the PMSQ surface and the buried PMSQ/silicon interface.…”
Section: Applications Of Sfg To Study Polymer Surfaces and Interfacesmentioning
confidence: 99%
See 1 more Smart Citation